Copper-induced activation of TRP channels promotes extracellular calcium entry and activation of CaMs and CDPKs leading to copper entry and membrane depolarization in Ulva compressa - Melissa eGómez; Alberto eGonzález; Claudio A. Sáez; Bernardo eMorales; Alejandra eMoenne (Frontiers in Plant Science, 2015)
In order to identify channels involved in membrane depolarization, Ulva compressa was incubated with agonists of TRP channels C5, A1 and V1 and the level of intracellular calcium was detected. Agonists of TRPC5, A1 and V1 induced increases in intracellular calcium at 4, 9 and 12 min of exposure, respectively, and antagonists of TRPC5, A1 and V1 corresponding to SKF-96365 (SKF), HC-030031 (HC) and capsazepin (CPZ), respectively, inhibited calcium increases indicating that functional TRPs exist in U. compressa. In addition, copper excess induced increases in intracellular calcium at 4, 9 and 12 min which were inhibited by SKF, HC and CPZ, respectively, indicating that copper activate TRPC5, A1 and V1 channels. Moreover, copper-induced calcium increases were inhibited by EGTA, a non-permeable calcium chelating agent, but not by thapsigargin, an inhibitor of endoplasmic reticulum (ER) calcium ATPase, indicating that activation of TRPs leads to extracellular calcium entry. Furthermore, copper-induced calcium increases were not inhibited by W-7, an inhibitor of CaMs, and staurosporine, an inhibitor of CDPKs, indicating that extracellular calcium entry did not require CaMs and CDPKs activation. In addition, copper induced membrane depolarization events at 4, 8 and 11 min and these events were inhibited by SKF, HC, CPZ and bathocuproine, a specific copper chelating agent, indicating copper entry through TRP channels leading to membrane depolarization. Moreover, membrane depolarization events were inhibited by W-7 and staurosporine, indicating that CaMs and CDPKs are required in order to activate TRPs to allow copper entry. Thus, light-dependent copper-induced activation TRPC5, A1 and V1 promotes extracellular calcium entry leading to activation of CaMs and CDPKs which, in turn, promotes copper entry through these TRP channels leading to membrane depolarization.